2023
DOI: 10.1007/s10826-023-02551-x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles, Family Characteristics, and Teacher-Reported Behavioral Outcomes in Kindergarten

Abstract: It is well established that parenting influences child behavior at home, but less is known about the associations between parenting and teacher reports of child behavior at school, an environment more distal from the home context. This study investigated the presence of authoritarian, authoritative, permissive, and uninvolved parenting styles (PS) in a community sample of 321 parents with kindergarteners (M age = 5.45 years) in the Northwestern United States. This study analyzed (1) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“… 17 In addition, the parents’ own psychological problems (such as anxiety and depression) may also affect their parenting style, increasing the risk of children suffering from OCD to some extent. 18 Research has shown that parenting styles are significantly associated with parenting stress and childhood problematic behaviors, 19 and error monitoring might be a bridging factor between parenting styles and psychological resilience. 20 The overall hypothesis is that overcompensation and avoidance coping styles negatively impact upon eating attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“… 17 In addition, the parents’ own psychological problems (such as anxiety and depression) may also affect their parenting style, increasing the risk of children suffering from OCD to some extent. 18 Research has shown that parenting styles are significantly associated with parenting stress and childhood problematic behaviors, 19 and error monitoring might be a bridging factor between parenting styles and psychological resilience. 20 The overall hypothesis is that overcompensation and avoidance coping styles negatively impact upon eating attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%